Internet usage from Islamic perspective: a preliminary survey with first year medical students, Kuantan Campus, Pahang 2015 - Swe, Swe Latt; U Tun Aung, Maulana Akbar Shah (IJRITCC, 2015)
Background: The internet today has become a greater part of every citizen‘s life which helps many successful, although, many fall in failure if not utilize it carefully. The usage of the Internet is bringing welfare of mankind while avoiding different types of drawback, many of us unable to identify it. This study measured the level of Internet addiction (IA) among students and explored their perspectives on using the Internet based on religious background. Methods: A cross-sectional descriptive study was done at IIUM, Kuantan Campus, Pahang in July 2015. A total of 103 first year medical students was organized purposely. Internet addiction of the participants was assessed using online questionnaires containing Internet Addiction Test-20. Benefits (7-items) and disadvantages (5-items) Internet usage from Islamic perspective was analysed with (12) relevant questionnaires pertaining basic themes of Islam such as, ―Islamic Religion, Ibadah, Greeting, Social Responsibility, Muslim‘s Issues, Ummah, Da‘wah, Islamic Business, Al Quran, Hadith, Sunna, Islamic Study‖. Results: Prevalence of normal (5.8%, n=6), mild IA (48.5%, n=50), moderate IA (44.7%, n=46) and severe IA (1%, n=1) were resulted respectively. Mean (SD) age of students was 20.9 (0.5) years, 35.9% male, 64.1% female, 96.1% residents at dormitory, 48.5% using the Internet more than 7 years, 64.1% spend on line 2 to 5 hours/day and 78.6% Smartphone users. Regarding Islamic perspective, 80% of the users acknowledged that Internet usage can provide benefits in enhancing Islamic knowledge, while 20% disagreed with regarding positive Internet usages. For negative usages of the Internet, 60% of the users approved as negative and 40% recognized as it was beneficial. Conclusion: Internet usage has been proven to be beneficial to all Muslims and it can be an effective tool for Da‘wah activities, but it is highly recommended that it has to be utilized with a great caution while keeping the importance of the concept of Islamic teaching. Key words: Internet Addiction, Islamic perspective, medical student, misconception, Da’wah